Socio-Economic Situation of Coastal Communities in Blimbingsari Village, Blimbingsari District, Banyuwangi Regency - Adinda Diah Adyaningrum; Asfarina Hidayah (Journal of Aquaculture Science, 2021)
Blimbingsari is a village area located in Banyuwangi Regency, East Java Province, Indonesia. Blimbingsari Village is an area in Banyuwangi Regency which consists of agricultural areas, villages and the coast. The life of the coastal community in Blimbingsari Village has a fairly good socio-economic condition and the existence of a coastal economy. The purpose of this study was to determine and study the socio-economic conditions of the coastal communities of Blimbingsari Village, Banyuwangi Regency. This research was conducted using descriptive analysis method by conducting qualitative analysis and quantitative analysis of primary data and secondary data obtained from sources. The results of the study indicate that the majority of coastal communities make a living as fishermen as many as 1,097 people. The catch of fishermen is usually the type of stingray (Dasyatidae) or other types of fish depending on the season. With an average (gross) income of Rp. 2,500,000 – Rp. 3,200,000 per month. The level of welfare of the coastal community of Blimbingsari can be said to be prosperous with a low unemployment rate and as many as 1,501 families listed in the village profile data in 2020 are recorded as prosperous families. Keywords: socio-economic conditions, coastal communities, Blimbingsari, Banyuwangi